Ethylene mediates dichromate‐induced inhibition of primary root growth by altering AUX1 expression and auxin accumulation in Arabidopsis thaliana. (June 2018) - Wakeel, Abdul; Ali, Imran; Upreti, Sakila; Azizullah, Azizullah; Liu, Bohan; Khan, Ali Raza; Huang, Linli; Wu, Minjie; Gan, Yinbo
Abstract: The hexavalent form of chromium [Cr(VI)] causes a major reduction in yield and quality of crops worldwide. The root is the first plant organ that interacts with Cr(VI) toxicity, which inhibits primary root elongation, but the underlying mechanisms of this inhibition remain elusive. In this study, we investigate the possibility that Cr(VI) reduces primary root growth of Arabidopsis by modulating the cell cycle‐related genes and that ethylene signalling contributes to this process. We show that Cr(VI)‐mediated inhibition of primary root elongation was alleviated by the ethylene perception and biosynthesis antagonists silver and cobalt, respectively. Furthermore, the ethylene signalling defective mutants ( ein2‐1 and etr1‐3 ) were insensitive, whereas the overproducer mutant ( eto1‐1 ) was hypersensitive to Cr(VI). We also report that high levels of Cr(VI) significantly induce the distribution and accumulation of auxin in the primary root tips, but this increase was significantly suppressed in seedlings exposed to silver or cobalt. In addition, genetic and physiological investigations show that AUXIN‐RESISTANT1 ( AUX1 ) participates in Cr(VI)‐induced inhibition of primary root growth. Taken together, our results indicate that ethylene mediates Cr(VI)‐induced inhibition of primary root elongation by increasing auxin accumulation and polar transport by stimulating the expression of AUX1. Abstract : Dichromate induces ethylene signalling and biosynthesis. Induced auxin accumulation in the primary root tip is mediated by Cr(VI)‐induced ethylene. Induced auxin accumulation is mediated by the Cr(VI)‐induced ethylene mediated AUX1 expression that is mediating inhibition of the primary root growth and development.